2014
DOI: 10.1002/chem.201402073
|View full text |Cite
|
Sign up to set email alerts
|

Pillar[5]arene‐Mediated Synthesis of Gold Nanoparticles: Size Control and Sensing Capabilities

Abstract: We present a simple procedure for the synthesis of quasi-spherical Au nanoparticles in a wide size range mediated by macrocyclic host molecules, ammonium pillar[5]arene (AP[5]A). The strategy is based on a seeded growth process in which the water-soluble pillar[5]arene undergoes complexation of the Au salt through the ammonium groups, thereby avoiding Au nucleation, while acting as a stabilizer. The presence of the pillar[5]arene onto the Au nanoparticle particle surface is demonstrated by surface-enhanced Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…Recently, Montes-García et al reported the synthesis of quasi-spherical Au nanoparticles in a wide size range, up to 120 nm in diameter through a seeded growth method using a water-soluble pillar [5]arene bearing ammonium groups (hereafter ammonium pillar [5]arene or AP[5]A) (Figure 11). [62] The pillar [5]arene tethered with water soluble ammonium groups could form a complex with the Au salt to avoid Au nucleation. They have proven that the AP [5]A is adsorbed onto the quasi-spherical Au nanoparticles with the pillar [5]arene cavity perpendicularly oriented to the metal surface.…”
Section: Pillararene-involved Metal Nanoparticlesmentioning
confidence: 99%
“…Recently, Montes-García et al reported the synthesis of quasi-spherical Au nanoparticles in a wide size range, up to 120 nm in diameter through a seeded growth method using a water-soluble pillar [5]arene bearing ammonium groups (hereafter ammonium pillar [5]arene or AP[5]A) (Figure 11). [62] The pillar [5]arene tethered with water soluble ammonium groups could form a complex with the Au salt to avoid Au nucleation. They have proven that the AP [5]A is adsorbed onto the quasi-spherical Au nanoparticles with the pillar [5]arene cavity perpendicularly oriented to the metal surface.…”
Section: Pillararene-involved Metal Nanoparticlesmentioning
confidence: 99%
“… Schematic representation of the different approaches for macrocycle‐stabilized metal nanoparticle synthesis: A) Thiacalixarenes as reductant and stabilizer; B) seeded‐growth approach based on pillararenes; and C) post‐synthetic surface modification based on thiol containing macrocycles. Adapted with permission from references 19, 28, 35, respectively. …”
Section: Synthesis and Surface Modification Of Metal Nanoparticlesmentioning
confidence: 99%
“…Recently, Montes‐García et al. proposed the synthesis of quasi‐spherical Au nanoparticles in a wide size range, up to 120 nm in diameter, through a seeded growth method using a water‐soluble pillar[5]arene bearing ammonium groups (Figure 2B) 28. This pillar[5]arene was found to complex the gold salt precursor thereby preventing Au nucleation.…”
Section: Synthesis and Surface Modification Of Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon the external stimulus application the polymer coating collapsed and the analyte would be brought into contact with [ [20] Host-guest interactions mediated by supramolecular chemistry has been also proposed to develop novel SERS sensing strategies. [21][22][23] Cyclodextrins, calixarenes, cucurbiturils, or pillararenes are important building blocks within supramolecular chemistry. [24][25] These macrocyclic molecules can be often straightforward synthesized in high yield and short reaction times.…”
Section: Introductionmentioning
confidence: 99%